Investigation on the Structure of Water/AOT/IPM/Alcohols Reverse Micelles by Conductivity, Dynamic Light Scattering, and Small Angle X-ray Scattering - Zhang, Xiaoguang; Chen, Yingjun; Liu, Jiexiang; Zhao, Chuanzhuang; Zhang, Haijiao (The journal of physical chemistry. B, 2012)
We have systematically investigated the effect of alcohols (ethanol, propanol, butanol, and pentanol) on the structure of the water/AOT/IPM system using conductivity, dynamic light scattering (DLS), and small-angle X-ray scattering (SAXS) techniques. The results show that no percolation phenomenon is observed in the water/AOT/IPM system, whereas the addition of ethanol (propanol and butanol) induces apparently percolation. The threshold water content (W p) depends closely on the alcohol type and concentration. The effect of alcohols on the conductance behavior is discussed from the physical properties of alcohols, the interfacial flexibility, and the attractive interactions between droplets. The hydrodynamic diameter of droplets (d H) obtained from DLS increases markedly with the increase in water content (W 0); however, it decreases gradually with increasing alcohol chain length and concentration. SAXS measurements display distinctly the shoulder, the low hump peaks, and the heavy tail phenomenon in the pair distance distribution function p(r) profile, which rely strongly on the alcohol species and its concentration. The gyration radius (R g) increases with increasing W 0, and decreases with the increase of alcohol chain length and concentration. Schematic diagram of the conductance mechanism of water/AOT/IPM/alcohol systems is primarily depicted. Three different phases of the discrete droplets, the oligomers, and the isolated ellipsoidal droplets existed in the different W 0 ranges correspond to three different stages in the conductivity–W 0 curve. Coupling the structure characteristics of reverse micelles obtained from DLS and SAXS techniques with conductivity could be greatly helpful to deeply understand the percolation mechanism of water/AOT/IPM/alcohols systems.